The value of chromosome instability detected by low−pass whole−genome sequencing in preoperative prediction of sentinel lymph node metastasis in breast cancer - Zheng, Jian; Xu, Fen; Li, Guangying; Lin, Moubin; Hao, Hua (Frontiers in Oncology, 2024)
BackgroundBreast cancer is a malignancy characterized by chromosomal instability (CIN). This study aimed to examine the potential diagnostic value of chromosomal instability, detected by low-pass whole-genome sequencing (LPWGS), in the preoperative evaluation of sentinel lymph node metastasis (SLNM) in breast cancer.MethodsA retrospective investigation of clinical records from 29 patients with breast cancer revealed two distinct groups based on sentinel lymph node biopsy (SLNB) results: the SLN metastasis group (24 cases) and the SLN non-metastasis group (five cases). CIN and CIN scores were evaluated using LPWGS. An analysis of univariate data and binary logistic regression was employed to identify factors influencing SLNM, and a curve with receiver operating characteristics (ROC) was constructed to assess the diagnostic utility of CIN in predicting SLNM.ResultsA significant association between the SLNM and CIN high groups was observed in breast cancer (P=0.011). The CIN score in the metastasis group (17,665.055 ± 8,630.691) was higher than that in the non-metastasis group (9,247.973 ± 3,692.873), demonstrating a significant difference (P=0.044). Univariate binary logistic regression analysis indicated that CIN was a significant predictor for SLNM (odds ratio: 4.036, 95% CI: 1.015–16.047, P=0.048). The AUC of CIN for preoperative diagnosis of SLNM was 0.808 (95%CI: 0.635–0.982, P=0.033), with a sensitivity value of 67.0% and specificity of 100.0% at a threshold of 13,563.ConclusionDetecting CIN through LPWGS demonstrates diagnostic potential in predicting SLNM in patients with breast cancer before surgery. This approach offers a novel method for assessing axillary lymph node status in clinical practice.